Uncovering Metagovernance in Government- Third Sector Collaboration in Kano State, Nigeria (Journal of Governance and Development (JGD), 2020)
Uncovering metagovernance in collaborative settings in Kano state, Nigeria, is the main concern of this paper. The central question explored was, what were the governing frameworks used by government policy officials and third sector chief executives (CEOs) to metagovern collaboration in the resource constrained state? This question was explored using an interpretivist qualitative research design that involved in-depthinterview sources and document analysis. The interviews consisted of a total of 12 participants, six government policy officials and six third sector chief executives, and, in each case, lasted an hour-and-the-half, in three cycles, over a period of three months. The interviews were analysed with the aid of NVivo-8 software as a data processing tool. The study findings suggest that although there was no standard framework for governing collaboration that could be described as systematic metagovernance, pragmatic combinations of a dominant ‘dynamic approach’ and an emerging ‘stable approach’ were employed to govern government-third sector collaboration in the state. Despite the limitations of this approach, it had prevailed in collaborative settings in the state for at least two decades and now urgently requires replacement. The paper concludes that for collaboration to be effective in delivering public services and publicly desired outcomes, key features of the dynamic and the stable approach to collaboration must be merged to co-create an innovative and resilient metagovernance system that will serve all actors involved in co-construction and co-creation activities in the state.